54.2k views
3 votes
What is the solution to the equation 3(х – 1) – 2(2x + 1) = 8(х-1)?

1 Answer

2 votes

Answer: x=
(4)/(7)

Explanation:

1. Remove parentheses.

3(x-1)-2x-1=8(x-1)3(x−1)−2x−1=8(x−1)

2.Expand.

3x-3-2x-1=8x-83x−3−2x−1=8x−8

3. Simplify 3x-3-2x-13x−3−2x−1 to x-4x−4.

x-4=8x-8x−4=8x−8

4. Subtract xx from both sides.

-4=8x-8-x−4=8x−8−x

5. Simplify 8x-8-x8x−8−x to 7x-87x−8.

-4=7x-8−4=7x−8

6. Add 88 to both sides.

-4+8=7x−4+8=7x

7. Simplify -4+8−4+8 to 44.

4=7x4=7x

8. Divide both sides by 77.


(4)/(7)=x

​9.Switch sides.

x=
(4)/(7)

​​

User Fenomas
by
6.2k points